Chemiresistors: Transistor‐Like Modulation of Gold Nanoparticle Film Conductivity Using Hydrophobic Ions (Adv. Mater. Interfaces 5/2014). Issue 5 (August 2014) - Chow, Edith; Raguse, Burkhard; Müller, Karl‐H.; Wieczorek, Lech; Cooper, James S.; Hubble, Lee J.; Webster, Melissa S.
<x xml:space="preserve">Abstract</x> Functionalized gold nanoparticle films are wellknown to act as chemically‐sensitive resistors (i.e., passive electrical components). B. Raguse, E. Chow, and co‐workers report in article 1400062 that such nanoparticle films are also capable of being used as chemically‐sensitive, active (transistor‐like) components by applying an external gate potential in the presence of hydrophobic ions. An immediate application is the development of highly sensitive sensors where the sensitivity towards charged molecules is improved by several orders of magnitude. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>